PREIMPLANTATION GENETIC SCREENING OF EMBRYOS IN THE PROCESS OF IN VITRO FERTILIZATION - PILOT STUDY - Stojić, Ivana; Vukosavljević, Jelena; Maričić, Slobodan; Vuković, Miloš R; Stojanoski, Stefan; Trninić Pjević, Aleksandra (Medicinski podmladak, 2019)
Introduction: Ever since the first successful in vitro conception was made, the selection of the most competent embryos for transfer was the primary focus of research in this domain. The main cause of implantation failure and pregnancy loss is the presence of aneuploidy. It has been proposed that the performance of the in vitro fertilization (IVF) can be improved by selection and transfer of the embryo without chromosomopathy. This method is known as Preimplantation Genetic Screening (PGS). Aim: The aim of our study was to determine the clinical significance of the array comparative genomic hibridization (array CGH) within the PGS and the possibility of routine application of PGS to determine the existence of aneuploidy within the embryos obtained in IVF procedure. Material and methods: We performed partly both retrospective and prospective study on 25 patients who underwent an IVF with PGS in the Clinic for Gynaecology and Obestetrics, Clinical Center of Vojvodina, from March 2015 to Februrary 2016. Embryo biopsy was done first, and then the samples were sent to the Institute for Health Protection of Children and Youth of Vojvodina, where array CGH method was performed. Results: From 109 analyzed samples, 63 were successfully amplified, while 46 were not. From those successfully amplified, 26.98% (17/63) were euploid and 73.02% (46/63) aneuploid. The percentage of aneuploidy was highest in patients in the age group 31-36 years (50%; 23/46). Patients with tubal infertility had the highest rate of aneuploidy (36.9%; 17/46). Conclusion: In our study, aneuploidies were present in a high proportion in patients with tubal sterility and in patients in the age group 31-36 years, which significantly reduces the chance of a successful IVF procedure. Routine screening of embryos for aneuploidies in an IVF procedure would significantly reduce emotional, financial and time losses.